Expression of VINV1, SCB1 and SCS1 genes in the seed coats of contrasting soybean seeds - Bahry, Carlos; Zimmer, Paulo (Revista Ciência Agronômica, 2014)
The seed coat is vital for the proper development of soybean seeds and also, after their physiological maturity, for providing protection against various biotic and abiotic factors. The aim of this work was to evaluate the relative expression of three candidate genes, VINV1, SCB1 and SCS1, which are possibly involved in seed quality, in the contrasting seed coats of four soybean genotypes. Two yellow seed coat genotypes, BMX Potência RR and CD 202, and two black seed coat genotypes, TP and IAC, were used. Relative gene expression was evaluated by the qPCR technique for seven phases of seed coat development in the four genotypes, at 25, 30, 35, 40, 45, 50 and 55 days after anthesis. The design was completely randomised, with three replications. Data were subjected to variance analysis and the means were compared by Tukey test at 5% probability. The VINV1 and SCS1 genes exhibit greater expression in the early stages of seed coat development in the cultivar BMX Potência RR. The SCB1 gene displays greater expression in the cultivar CD 202, also in the early stages of seed coat development. The three genes under study show greater expression in yellow seed coat genotypes.